TINGKAT NASIONALISME ANGGOTA EKSTRAKURIKULER SANGGAR SENI AGAWE SANTOSO SMAN 1 SINGGAHAN TUBAN - Miftahul Jannah; Listyaningsih Listyaningsih (Kajian Moral dan Kewarganegaraan, 2023)
This study aims to determine the level of nationalism of the extracurricular members of Sanggar Seni Agawe Santoso at SMAN 1 Singgahan Tuban. The research uses Coleman's rational choice theory. According to Coleman, actors are considered as individuals who have goals, actors also have a choice of basic value to be used to determine the choices and actions they want. This research uses quantitative research with descriptive design. Data collection techniques using a questionnaire filled out by 42 members. Analysis of the data used is to find the highest percentage of extracurricular members and the lowest. The results showed that the level of nationalism of the members of the Sanggar Seni Agawe Santoso extracurricular SMAN 1 Singgahan Tuban was 48% in the middle position. Extracurricular members of the Agawe Santoso Art Studio at SMAN 1 Singgahan Tuban have a moderate level of nationalism. This factor was found that the members still do not fully love the local culture. This is obtained because the members still have a sense of participating in preserving, developing and introducing their local culture.